2009
DOI: 10.1093/ndt/gfp472
|View full text |Cite
|
Sign up to set email alerts
|

Tempol or candesartan prevents high-fat diet-induced hypertension and renal damage in spontaneously hypertensive rats

Abstract: Our study suggests that a high-fat diet induces fatty kidneys, aggravation of blood pressure and renal inflammation in the SHR. Blockade of oxidative stress by tempol or of RAS by candesartan ameliorates the increase in blood pressure and renal inflammation and improves intrarenal lipid accumulation. Therefore, antioxidants or angiotensin receptor blockers can prevent diet-induced hypertension and renal inflammation in hypertensive rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 54 publications
2
48
0
2
Order By: Relevance
“…However, it has been demonstrated that a HFD increased body weight, serum cholesterol, and BP in SHRs and the changes in metabolic parameters were associated with cardiovascular dysfunction in these animals (Šedová et al 2004(Šedová et al , Cao et al 2011. Chung et al (2010) have shown that after 12 weeks on the HFD, SHRs gained more body weight, their systolic BP was further elevated, and glucose intolerance induced, but there were no significant differences in the insulin resistance index, serum lipid profile, plasma renin activity, and serum aldosterone levels. On the other hand, Knight et al (2008) observed that HFD consumption for 10 weeks had no effect on systolic BP of SHRs.…”
Section: Rat Models Of Obesity and Hypertensionmentioning
confidence: 96%
“…However, it has been demonstrated that a HFD increased body weight, serum cholesterol, and BP in SHRs and the changes in metabolic parameters were associated with cardiovascular dysfunction in these animals (Šedová et al 2004(Šedová et al , Cao et al 2011. Chung et al (2010) have shown that after 12 weeks on the HFD, SHRs gained more body weight, their systolic BP was further elevated, and glucose intolerance induced, but there were no significant differences in the insulin resistance index, serum lipid profile, plasma renin activity, and serum aldosterone levels. On the other hand, Knight et al (2008) observed that HFD consumption for 10 weeks had no effect on systolic BP of SHRs.…”
Section: Rat Models Of Obesity and Hypertensionmentioning
confidence: 96%
“…53 There is evidence which suggests that a high-fat diet induces renal inflammation and aggravation of blood pressure via ROS in spontaneously hypertensive rats. 54 Additionally, metabolic syndrome is a risk factor for chronic kidney disease (CKD) that is at least in part independent of diabetes and hypertension and probably mediated by ROS. Moreover, the onset and maintenance of renal damage may worsen metabolic syndrome features, such as hypertension, leading to potential vicious cycles.…”
Section: Urotensin-iimentioning
confidence: 99%
“…42 For example, an upregulation of reactive oxygen species appeared to precede the development of hypertension, 43,44 and an antioxidant regimen arrested the process. 44,45 In vasculature, the major source of reactive oxygen species was from a family of non-phagocytic NAD(P)H oxidases, which comprised a catalytic core (Nox/p22 phox ) and several cytosolic subunits (p47 phox , p67 phox , p40 phox , Rac). 46 The core and the subunits heterodimerized in response to physiological and pathological stimulation such as angiotensin II (Ang II), 47 thereby facilitating superoxide (that is, O 2 À ) production.…”
Section: Molecular Targets Of Chlorogenic Acid In Blood-pressure Regumentioning
confidence: 99%